Conductive and Stable Magnesium Oxide Electron‐Selective Contacts for Efficient Silicon Solar Cells. Issue 5 (16th November 2016) - Wan, Yimao; Samundsett, Chris; Bullock, James; Hettick, Mark; Allen, Thomas; Yan, Di; Peng, Jun; Wu, Yiliang; Cui, Jie; Javey, Ali; Cuevas, Andres
Abstract : A high Schottky barrier (>0.65 eV) for electrons is typically found on lightly doped n‐type crystalline (c‐Si) wafers for a variety of contact metals. This behavior is commonly attributed to the Fermi‐level pinning effect and has hindered the development of n‐type c‐Si solar cells, while its p‐type counterparts have been commercialized for several decades, typically utilizing aluminium alloys in full‐area, and more recently, partial‐area rear contact configurations. Here the authors demonstrate a highly conductive and thermally stable electrode composed of a magnesium oxide/aluminium (MgO x /Al) contact, achieving moderately low resistivity Ohmic contacts on lightly doped n‐type c‐Si. The electrode, functionalized with nanoscale MgO x films, significantly enhances the performance of n‐type c‐Si solar cells to a power conversion efficiency of 20%, advancing n‐type c‐Si solar cells with full‐area dopant‐free rear contacts to a point of competitiveness with the standard p‐type architecture. The low thermal budget of the cathode formation, its dopant‐free nature, and the simplicity of the device structure enabled by the MgO x /Al contact open up new possibilities in designing and fabricating low‐cost optoelectronic devices, including solar cells, thin film transistors, or light emitting diodes. Abstract : A highly conductive and thermally stable electrode composed of a nanoscale magnesium oxide/aluminium (MgO x /Al) contact is demonstrated to achieve moderately low resistivity Ohmic contacts on lightly doped n‐type c‐Si. A power conversion efficiency of 20% is obtained at a proof‐of‐concept stage of n‐type c‐Si solar cells with full‐area MgO x /Al rear contacts.